The Levels of Satisfaction Consumer Herbal Slim Product: An Customer Satisfaction Index (CSI) Approach - Nafi'ah, Aminatun; Munambar, Siwitri; Sadiyah, Fitria Naimatu (University of Jember, 2023)
Marketing activities on slimming herbal products have not been optimized. The condition of intense competition and the lack of purchasing power of products, shows that consumers are increasingly selective in determining product choices. This study aims to (1) analyze the level of importance and performance of slimming herbal product attributes and (2) measure the level of satisfaction of slimming herbal products. This research was conducted from January to July 2023. Location determination was carried out by purposive sampling and a total of 30 respondents were determined by convenience sampling. The data collection technique was carried out by filling out questionnaire. Data analysis was carried out using the Importance Performance Analysis (IPA) method in 4 quadrants, with the x-axis stating performance and the y-axis describing importance. describes importance. While the calculation of Customer Satisfaction Index (CSI) calculations are used to determine customer satisfaction criteria. The results of the study obtained the level of performance and importance that require improvement, namely in quadrant I (high level of importance with low performance) and quadrant III (low level of importance with low performance),, while the attributes that need improvement are price and promotion. The results of level customer satisfaction shows 83.6% in the criteria very satisfied.